Virtual COVID-19 Clinical Teaching Session:: A Substitute for ‘Sheltered in Place’ MedicalStudents - Jessica Allman; Mohamad Moussa; Shivam Shah; Madison Rectenwald; Casey Pollard; Jake Goliver (Translation: The University of Toledo Journal of Medical Sciences, 2020)
The novel SARS-CoV-2 virus, or COVID-19, has caused a pandemic in the past year that has significantly impacted the health care system and medical education. This virus has uniquely impacted Emergency Medicine, as many COVID-19 patients suffer from acute respiratory distress or failure and require emergent stabilization. While physicians, residents, and medical students would all benefit from hands-on training on the medical management and stabilization of COVID-19 patients, this is not feasible due to risk of transmission and spread of the virus. Students have missed countless hours of hands-on clinical education because of the shift to online learning or emergency remote learning due to these concerns. A PowerPoint presentation was given via Webex by Emergency Medicine physicians and residents to medical students in hopes of bridging this gap. The lecture presented information on diagnosis, clinical management, and clinical course of COVID-19 positive patients in the Emergency Department. Students were able to engage with Emergency Medicine physicians and ask questions in real time. A pre-session survey and post-session survey were administered via Google Forms to assess students’ confidence in six different domains. There was significant improvement in all six domains of the survey when comparing the pre-session and post-session survey confidence intervals with a p<0.05 being statistically significant. It was found that storytelling of patient management was an effective way to demonstrate clinical skills critical for physicians such as advocating for patients. This presentation highlights the utility and effectiveness of an interactive approach to the virtual education of medical students during the COVID-19 pandemic while adhering to online learning and social distancing formats. In addition, this model can be applied to substitute for other clinical learning opportunities that are not currently available to students due to the pandemic.